Improvement of Knowledge and Giving Motivation in Implementing a Healthy Life Community - Susyana Candra Santi Dewi (Jurnal Peduli Masyarakat, 2020)
Indonesia is faced with a triple burden disease. The high level of infectious diseases, the increase in non-communicable diseases, and the reappearance of diseases that should have been overcome become health problems that must be considered. The existence of the problems that exist it is necessary to understand the movement of the community to live healthy. Service to the community was carried out on the mothers of the Taklim Assembly Ummu Salamah in Minggiran Village. The implementation method used to overcome the problem uses health education about the healthy living community movement (Germas) with leaflet instruments. Assessment of the results of knowledge using Microsoft Excel in its processing. The results of community service have shown that the participants' knowledge has increased, this is in line with the motivation in the implementation of the healthy living community movement after health education about the healthy life community movement (germas) for the mothers of Taklim Assembly, Ummu Salamah, Minggiran Village.